The Uniform International Keyword 'Reasonable'; Pathfinder or Insurmountable Obstacle for a Uniform Application of the CISG? - An Examination of Case law - - Linnemannstoens, Heike (Department of Commercial Law, 2014)
The United Nations Convention on Contracts for the International Sale of Goods1(CISG) entered into force on 1 January 1988. It is the uniform international sales law of countries that account for over two-thirds of all world trade.2 As of 17 November 2005, the United Nations reports that 66 States have adopted the CISG.3 One of the keyarticles of the CISG is Article 7 (1) CISG. It requires regard to the international character of the Convention and to the need to promote uniformity in its application and the observance of good faith in international trade. Article 7 (1) CISG raised a lot of hope that the provisions and terms of the CISG are interpreted in the same way by the practitioners of the CISG. Leading scholars classified the CISG as a chance for a common international language.4 Some general terms incorporated in the CISG seem to dash this hope. As the Convention forms part of the UN regime there is no supranational instance or Court of uniformity. Problems of uniformity must therefore be tackled in the domestic domain.5 Especially general terms are imputed to provide problems of uniformity because of discrepancies in domestic practice.